The Connection Between Stress and Women’s Smoking During the Perinatal Period: A Systematic Review - M. Carmen Míguez; Yara Queiro; Cristina M. Posse; Alba Val (Brain Sciences)
Introduction. In women, smoking during pregnancy and the postpartum period has important consequences for maternal and infant health, and interventions to assist smoking cessation during this period are essential. Although smoking has been associated with the presence of mental health problems, few studies addressing the factors associated with perinatal smoking have examined the role of stress. The aim of this review was to identify the relationships between the presence of stress and smoking during pregnancy and the postpartum period. Method. A literature search of the PsycInfo, Pubmed and Web of Science databases was carried out to identify relevant articles published between January 2013 and June 2024. A total of 15 studies that met the inclusion criteria were selected for review. Results. Twelve of the studies analysed the relationship between stress and smoking during pregnancy, two studies involved the postpartum period, and one study included both periods. Diverse instruments were used to assess stress, although the PSS-14 was the most commonly used. Eleven of the studies found a relationship between stress and smoking in the perinatal period, with stress being a predictor of smoking. Conclusions. The findings highlight the need to consider stress management when developing effective interventions to help women quit smoking during pregnancy and maintain abstinence in the postpartum period.